MYCORRHIZAL GROWTH RESPONSE AND GLOMALIN PRODUCTION EFFECTED BY ARBUSCULAR MYCORRHIZAL FUNGI (AMF) AND NITROGEN OF ORGANIC MATERIALS ON CORN - Eti Farda Husin; Azwar Rasyidin, Eddiwal, Amrizal Saidi, (Universitas Andalas, 2015)
Symbiotic relationships between arbuscular mycorrhizal fungi (AMF) and plants can increase the capacity of plants to absorb nutrients and water from the soil by exploring micropores not accessible to plant roots. The arbuscular mycorrhizal symbiosis between plants and soil fungi improves phosphorus and nitrogen acquisition under limiting conditions. Recent discoveries indicate that AMF hyphae containing glomalin as glycoproteins and function unitinge the soil particles to form stable soil aggregates. Glomalin acts as an adhesive (glue) produced by AMF symbiosis with the host plant. The AMF is capable of taking nitrogen and other nutrients from a source of organic materials to produce glomalin which is transferred to the host plant. The study was conducted using nitrogen from forage materials of Tithonia (Tithonia difersifolia) which the AMF needs to produce glomalin. This study assess the need for organic N by AMF to the mycorrhizal growth effect and its effects on glomalin. The study use sterile medium sand and zeolite mixture (w/w 1:1) in pot culture experiments with the corn as the host. For treatments using N derived from Tithonia are five doses, namely 0, 10, 20, 30, and 40 mg of N Tithonia each pot. At Â the time of planting, the corn roots inoculated with AMF spores of the two species, namely Glomus luteum and Glomus versiforme. We show that a positive mycorrhizal growth response (MGR) was observed only in the dose of range 20 to 30 mg N. This response did not appear to be affected by high nitrogen supply. Our results also show that in Glomus luteum at the dose of 20 mg N produce glomalin highest, namely 2.60 mg.g-1 in the planting medium. Glomus versiforme has produced glomalin is 2.38 mg.g-1 at the dose of 30 mg N. The AMF species did not significantly affect the results of glomalin, while the use of N from forage materials of Tithonia significantly influenced the production of glomalin.